Implementation of Lesson Study as an Innovative Professional Development Model Among Malaysian School Teachers (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ This qualitative study explored the implementation of Lesson Study, a kind of teacher-directed and bottom-up approach of the Japanese model of teacher professional development in the Malaysian education context. It seeks to answer the question of how implementation of lesson study as an innovative professional development model among Malaysian school teachers influences teachersâ€™ pedagogical content knowledge, and what school-based factors support or hinder the implementation of lesson study in the Malaysian context. Methodology â€“ The case study method was employed involving two secondary schools in the state of Kedah. Each school set up a lesson study group as a case. Case A had 9 teachers while case B had 8. The participants of both cases engaged themselves in the lesson study process for a period of 12 months. Each lesson study cycle required the participants to collaboratively plan, discuss, teach, observe and reflect on a particular lesson. Due to various constraints, at the end of this study, case A conducted three lesson study cycles while case B conducted only two cycles. Multiple data sources were gathered through in-depth interviews, observations, group discussions and reflections as well as participantsâ€™ journal writing. Findings â€“ The analysis of the qualitative data indicated that the lesson study group setting provided an encouraging opportunity and venue for the participants to collaborate, discuss and share their teaching knowledge and experiences. Consequently, the participants expressed that their content knowledge and pedagogical content knowledge were enhanced. They became more reflective and keener in promoting active student participation in their lessons. Significance â€“ This study revealed that the degree of knowledge enhancement was dependent upon each participantâ€™s attitude and commitment towards the teaching profession. However, when provided with sufficient supporting factors such as positive support from the school administrators, committed and dedicated group leaders and strong collegiality among the lesson study team, lesson study could be successfully implemented as an effective and innovative mode of teachersâ€™ professional learning.